ANALISIS ASPEK KESEHATAN DESA: PERAN MEDIA, PENGETAHUAN, KINERJA, FAKTOR PENDUKUNG, DAN EVALUASI PROGRAM - Dinopawe, Asriaty (Pasapua Health Journal, 2023)
Introduction: Village health is an integral benchmark that includes knowledge, performance, health promotion, and community participation in an effort to organise competitive and sustainable health services at the local level. An in-depth understanding of the aspects of village health will lead to improved community wellbeing. Methods: The method used in this study was literature review. Results: The results of this study indicate that there is a significant effect of pocket book provision on knowledge, knowledge does not significantly affect the performance of village midwives while Job description has a very significant effect on midwife performance, there is a relationship between predisposing, enabling, reinforcing factors with the implementation of the Maternal and Child Health Promotion Programme (MCH). Then the use of Community-Sourced Health Efforts (UKBM) has various reasons with the dominant not needing. Furthermore, the implementation of the Village Health Forum (FKD) in Gulon Village has not been sufficiently supportive of the “Active Alert Village” development programme due to a lack of required resources and poor FKD management. Conclusion: The 5 aspects of village health that are influential are the pocket book, job description, knowledge factors, health facilities and personnel in improving community health welfare